Antibacterial Resistance. The Challenge of Modernity - A. D. Daudova; Ju. Z. Demina; G. N. Genatullina; R. O. Abdrakhmanova; G. R. Baeva; A. L. Yasenyavskaya; O. V. Rubalsky (Антибиотики и Химиотерапия)
Antimicrobial resistance is considered by WHO as one of the most important threats to public health in the twenty-first century. According to forecasts, by 2025, many first-line antimicrobials will lose their effectiveness and the «post-antibiotic era» will begin. Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and representatives of the genus Mycobacterium are classified by the American Society of Infectious Diseases as microorganisms that play a predominant role in the development of infections associated with medical care and leading to fatal consequences. The review highlights the mechanisms of antibiotic resistance and many variants of microbial resistance to antibiotics. Knowledge of the molecular mechanisms of the formation of resistance of microorganisms allows us to develop strategic directions for overcoming it. The search for new ways to prevent and overcome the formation of resistance of pathogens to antibiotics is an extremely important task of modern medical science. The effectiveness of hybrid antibiotics associated with chemical compounds with various specific effects is presented. The use of the main active factor of the bacterial virus, endolysin, both in its pure form and as part of homodimers, for example, lysoprotein, which is a complex of endolysin with human immunoglobulins, is considered promising. Phage therapy of the future is a personalized phage therapy that requires the creation of a library or bank of phages.